Respuesta :

Answer:

[tex](p -5q)(p^{2}+5pq+25q^2})[/tex]

Step-by-step explanation:

The given expression is:

[tex]p^{3}-125q^3[/tex]

The related formula is:

[tex]a^3-b^3=(a-b)(a^{2}+ab+b^{2})[/tex]

We can transform the given expression in the form of a³ - b³ as shown below:

[tex]p^{3}-125q^3\\= p^{3} - 5^{3}q^{3}\\=p^{3}-(5q)^{3}[/tex]

Now here a = p and b = 5q. Using the above factorization, we get:

[tex]p^{3}-125q^{3}\\\\ = p^{3}-(5q)^{3}\\\\ = (p -5q)(p^{2}+5pq+25q^2})[/tex]

Answer:

(p-5q)(p^2+5pq+25q^2)

Step-by-step explanation:

ap3x

ACCESS MORE